2011
DOI: 10.1016/j.jaci.2011.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Thiol redox disturbances in children with severe asthma are associated with posttranslational modification of the transcription factor nuclear factor (erythroid-derived 2)–like 2

Abstract: Rationale Airway thiol redox disturbances, including depletion of the antioxidant, glutathione (GSH), are differentiating features of severe asthma in children. Objectives Given the role of the transcription factor, Nrf2, in maintaining GSH homeostasis and antioxidant defense, we quantified expression and activity of Nrf2 and its downstream targets in the airways and systemic circulation of asthmatic children. We hypothesized that Nrf2 activation and function would be impaired in severe asthma, resulting in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 45 publications
0
65
1
Order By: Relevance
“…16 Although some studies have used plasma GSH E h as a marker of intracellular redox, 44,45 we did not observe significant correlations of Hcys or SAH with plasma GSH E h , which suggests that whole blood GSH E h might be a better indicator of the intracellular redox environment, at least within blood cells. However, an oxidized plasma GSH E h is thought to reflect oxidative stress in other tissues 46 or systemic oxidative stress 47 and is observed in aging, 48 obesity 49 and disease states such as asthma 50 and heart disease. 51 Indeed, we found that plasma GSH E h , but not blood GSH E h , was positively correlated with age (Spearman r = 0.14, p = 0.01) and BMI (Spearman r = 0.11, p = 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…16 Although some studies have used plasma GSH E h as a marker of intracellular redox, 44,45 we did not observe significant correlations of Hcys or SAH with plasma GSH E h , which suggests that whole blood GSH E h might be a better indicator of the intracellular redox environment, at least within blood cells. However, an oxidized plasma GSH E h is thought to reflect oxidative stress in other tissues 46 or systemic oxidative stress 47 and is observed in aging, 48 obesity 49 and disease states such as asthma 50 and heart disease. 51 Indeed, we found that plasma GSH E h , but not blood GSH E h , was positively correlated with age (Spearman r = 0.14, p = 0.01) and BMI (Spearman r = 0.11, p = 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…NRF2 is a redox-sensitive basic leucine zipper transcription factor whose expression was initially reported to be reduced in the lungs following allergen exposure in mice and NRF2 knockout mice displayed enhanced allergen-driven airway infl ammation and hyperresponsiveness post ovalbumin exposure (Rangasamy et al, 2005). Altered oxidant responses have been seen particularly in severe asthma and this has been related to post-translational modifi cations of NRF2 which altered its ability to switch on anti-oxidant genes (Fitzpatrick et al, 2011). NRF2 activation is also involved in infl ammatory gene expression following bacterial lipopolysaccharide (LPS)-stimulation of airway epithelial cells and macrophages , controls eotaxin/CCL11 expression and release from airway fi broblasts (Fourtounis et al, 2012) and proliferation of airway smooth cells (Michaeloudes et al, 2011).…”
Section: Nrf2 Transcription Factor In Asthmamentioning
confidence: 99%
“…Earlier, Fitzpatrick et al (2011) showed that children with severe asthma have elevated NFE2L2 mRNA and protein levels as a function of increased thiol oxidation, but this increase has no effect on the downstream components of the antioxidant pathway, suggesting a posttranslational modification. One of the possible explanations for the NFE2L2 dysfunction and redox disturbances in severe asthma is the presence of single nucleotide polymorphisms in the NFE2L2 promoter.…”
Section: Discussionmentioning
confidence: 99%